Intensi Migrasi Mahasiswa dan Fenomena “Kaburajadulu” Analisis Regresi Logistik pada Mahasiswa Universitas Sriwijaya - Angra Aldora; Dian Cahyawati; Oki Dwipurwani; Eka Susanti; Des Alwine (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study is motivated by Indonesia’s efforts to accelerate the achievement of the Indonesia Golden Vision 2045 by optimizing the demographic bonus as a foundation for national development. The success of this vision depends on the availability of competitive and high-quality human resources. However, the growing migration intention among young generations, reflected in the “#KaburAjaDulu” phenomenon, raises concerns about potential brain drain if not properly managed. University students, as future educated human capital, play a strategic role in national development. This research aims to examine students’ perceptions toward migration intention and to develop a probabilistic model using binary logistic regression. A quantitative approach was applied using primary data collected through questionnaires distributed to Universitas Sriwijaya students. The response variable is migration intention, while predictor variables include economic, financial, social, political, career, self-development, quality of life, and public facilities factors. Descriptive analysis shows that students with migration intentions generally have unfavorable perceptions of most predictor variables, while political factors display relatively balanced responses between students with and without migration intentions. The analysis results indicate that several perception variables significantly influence migration intention. The obtained binary logistic regression model is . Financial and self-development factors increase the probability of migration intention, whereas political factors reduce it. These findings highlight financial perception as the dominant predictor influencing students’ intention to migrate abroad and provide empirical evidence to support talent management policies for sustainable national development.